The effectiveness of various type retaining wall to control coastal erosion - Mohamad Amirulanwar, Tumirin (2019)
Coastal erosion can be defined as the loss of the sand along the coastal area because of the action of waves, current or tides in a long duration of time. Coastal erosion happened when the water waves, currents or tides removed a portion of sand from the coastal area. When the water waves went to the coastal area, a portion of the number of the sand will be carried along from the coastal area when the waves return back to the sea, depositing and storing the sand in the formed of large sandbars. In a long duration of times following the water waves, the sand will return back to the coastal area. Due to the different in volume of the sand that was carried from the coastal area and the sand that are returned back to the coastal area in a repeated cycle caused the coastal erosion to happened. The main objective of this study is to identify the effectiveness of the various types retaining wall that are used for coastal protection today. The study was conducted in laboratory with four different types of retaining walls; vertical type, slope type, stairs type and curved type. The lab scale model is developed and constructed for the study in order to achieve the objective of the study by using the scale of 1:60 with assumption of the prototype retaining wall that has the height of 3 m. Among of the four types of retaining wall model that are used in this study, it found that the curved type is the most effective retaining wall model which it only allowed the lowest volume of water to pass through with an average rate overtopping volume of 1.67 ml/min. The result clearly showed that curved type retaining wall effectively able to protect the coastal area from wave attack. The less effective retaining wall from the study is sloped type which is indicated the highest volume of passing water over the walls with an average rate overtopping volume of 28 ml/min.